Water Losses During Technical Snow Production: Results From Field Experiments - Grünewald, Thomas; Wolfsperger, Fabian (Frontiers in Earth Science, 2019)
Alpine as well as Nordic skiing tourism strongly depend on the production of machine-made snow for the timely opening of the winter season. However, it is likely that sublimation, evaporation, wind drift, and the discharge of unfrozen water to the ground will result in the loss of significant parts of the water used. The relation between these water losses and the ambient meteorological conditions is poorly understood. We present results from a series of 12 detailed snow-making field tests performed in a ski resort near Davos, Switzerland. Water inflows, measured at the snow machine, are related to the mass of snow deposited on the ground. Snow amounts are calculated from accumulated volumes, measured with terrestrial laser scanning (TLS), and manually sampled snow densities. Additionally, samples of liquid water contents (LWCs) of the produced snow are presented. We find that 7 to 35 ± 7% (mean 21%) of the consumed water was lost during snow-making and that the loss is strongly related to the ambient meteorological conditions. Linear regression analysis shows that water losses increase with air temperature (TA). Combining our data with observations from earlier field measurements shows similar correlations.